Using redox potential as a feasible marker for banked blood quality and the state of oxidative stress in stored red blood cells. Issue 10 (23rd August 2021) - Daniels, Rodney C.; Jun, Hyesun; Davenport, Robertson D.; Collinson, Maryanne M.; Ward, Kevin R.
Abstract: Background: Stored red blood cells (RBCs) may undergo oxidative stress over time, with functional changes affecting oxygen delivery. Central to these changes are oxidation‐reduction (redox) reactions and redox potential (RP) that must be maintained for cell function. RP imbalance can lead to oxidative stress that may contribute to storage lesions. This study's purpose was to identify changes in RP over time in banked RBCs, and among RBCs of similar age. Methods: Multiple random RBC segments from RBC units were tested ( n  = 32), ranging in age from 5 to 40 days, at 5‐day intervals. RP was recorded by measuring open circuit potential of RBCs using nanoporous gold electrodes with Ag/AgCl reference. RP measures were also performed on peripheral venous blood from 10 healthy volunteers. RP measures were compared between RBC groups, and with volunteer blood. Results: Stored RBCs show time‐dependent RP increases. There were significant differences in Day 5 RP compared to all other groups ( p  ≤ 0.005), Day 10–15 vs. ages ≥ Day 20 ( p  ≤ 0.025), Day 20–25 vs. Day 40 ( p  = 0.039), and all groups compared to healthy volunteers. RP became more positive over time suggesting ongoing oxidation as RBCs age; however, storage time alone was not predictive of RP measured in a particular unit/segment. Conclusions: There are significant differences in RP between freshly stored RBCs and all others, with RP becoming more positive over time. However, storage time alone does not predict RP, indicating RP screening may be an important measure of RBC oxidative stress and serve as an RBC quality marker. Abstract : Redox potential (RP) measurements can provide a direct assessment of oxidative stress in stored red blood cells (RBCs). Utilizing these RP measures we present data demonstrating RBCs undergo increasing oxidation and oxidative stress over time while being stored. However, storage duration alone does not predict the redox potential of a given unit, indicating RP measurements may be a feasible marker of RBC quality and oxidative stress, while also providing a target by which to restore redox balance in stored RBCs prior to transfusion.